2023
DOI: 10.1101/2023.02.28.530428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adulis and the transshipment of baboons during classical antiquity

Abstract: Adulis, located on the Red Sea coast in present-day Eritrea, was a bustling trading centre between the first and seventh centuries CE. Several classical geographers––Agatharchides of Cnidus, Pliny the Elder, Strabo––noted the value of Adulis to Greco-Roman Egypt, particularly as an emporium for living animals, including baboons (Papiospp.). Though fragmentary, these accounts predict the Adulite origins of mummified baboons in Ptolemaic catacombs, while inviting questions on the geoprovenance of older (Late Per… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…As shown by previous work [44], the isotopic signature could also provide information on the animals' provenance where-in the case of the hamadryas baboons-it is hoped to find out whether the Horn of Africa or rather the southern part of the Arabian Peninsula played a role. Previous ancient DNA research has shown that genetic material is very poorly preserved, but mitochondrial DNA could also help determine provenance [57,77]. In addition, nuclear DNA could ascertain whether crossbreeding occurred between anubis and hamadryas baboons kept in captivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by previous work [44], the isotopic signature could also provide information on the animals' provenance where-in the case of the hamadryas baboons-it is hoped to find out whether the Horn of Africa or rather the southern part of the Arabian Peninsula played a role. Previous ancient DNA research has shown that genetic material is very poorly preserved, but mitochondrial DNA could also help determine provenance [57,77]. In addition, nuclear DNA could ascertain whether crossbreeding occurred between anubis and hamadryas baboons kept in captivity.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest among them is the female hamadryas baboon MHNL 51000172. The complete mitogenome of this individual was reconstructed and compared well with that of hamadryas from Eritrea, Ethiopia and eastern Sudan, although an origin from the Arabian Peninsula cannot be completely ruled out [57].This animal shows linear enamel hypoplasia (LEH) lines about halfway the crown of the first upper PLOS ONE and lower incisors. This marker may well correspond to the stress that the animal underwent when it was captured and translocated immediately afterwards.…”
Section: Import and Local Breedingmentioning
confidence: 99%
“…This is most evident in clades G1 and G4, which comprise both yellow and olive baboons, and clade G3, which comprises both olive and hamadryas baboons. It should be noted that the previously described northeastern olive clade G2 loses support with denser sampling and should be collapsed into clade G3 [ 48 ].…”
Section: The Two Main Clades Mingling: Past and Present Hybridization...mentioning
confidence: 99%
“…To develop a scenario of baboon phylogeographic history, we compiled georeferenced genetic data of modern baboons [ 18 , 35 , 37 , 48 , 50 , 51 , 68 ] and merged the phylogenetic reconstructions from these multiple datasets in a geographic context. The genus Papio is not well represented in the fossil record, but some key findings in southern and eastern Africa provide a crucial, additional context [ 69 , 70 , 71 , 72 , 73 ].…”
Section: A Comprehensive Phylogeographic Scenario For Baboonsmentioning
confidence: 99%
See 1 more Smart Citation